Avaliação qualitativa e quantitativa dos potenciais geoturístico e didático da bacia hidrográfica do Ribeirão Bom Jardim e da Serra do Bené, em Jaboticatubas – MG - Gabriel Luca Nascimento (2022)
The Ribeirão Bom Jardim, located in the State of Minas Gerais, in the city of Jaboticatubas, is a tributary of the Velhas and São Francisco rivers. Locally, it is used as a source of water collection for human consumption, family farming, animal watering and recreational activities. In addition, in Ribeirão Bom Jardim are located the Bené and Bom Jardim waterfalls, places attended by tourists due to the recreational water potential. The objective of this study is to evaluate the geotouristic and didactic potential of Ribeirão Bom Jardim and Serra do Bené. The applied methods comprise the qualitative and quantitative analysis of geodiversity sites and geodiversity spatialization, by calculating the relationships between capillarity, visibility, environmental fragility, and geodiversity index. There were seven geodiversity sites identified with both geotouristic and didactic potencial. The results indicate the possibility of geotouristic and didactic use of the evaluated sites and, from this, it was possible to propose a geotourist-didactic itinerary with accessible language to help teachers and local visitors.